Impact of on-field repeated sprint training on aerobic fitness and anaerobic performance in football athletes: A matched-pair design - Ramita Gupta; Moattar Raza Rizvi; Ankita Sharma; Shweta Sharma; Abdul Rahim Shaik; Mohamed K. Seyam; Shahid Raza; Mastour Saeed Alshahrani; Batool Abdulelah Alkhamis; Hani Hassan Alnakhli; Lama Moraya Alsalm; Fuzail Ahmad; et al. (PLoS ONE, 2025)
Background Repeated sprint ability (RSA) is essential for football performance, especially in maintaining high-intensity efforts throughout a match. Repeated sprint training (RST) improves both aerobic and anaerobic capacities; however, its effects on players in different positional roles remain underexplored, particularly with regard to tailored conditioning protocols. Objective This study assessed the impact of on-field RST on physical performance metrics, including aerobic capacity (VO₂max), sprint speed (10m DASH), vertical jump height (VJH), and power output, with a focus on positional differences among forwards, defenders, and goalkeepers. Methods Forty male football players (aged 18–25 years) were purposively sampled and matched by position before allocation into experimental (RST) and control groups. The experimental group completed a structured four-week RST program, while the control group continued routine football training involving technical, tactical, and endurance drills. Pre- and post-intervention assessments included the Cooper Test (aerobic capacity), VO₂max, VJH, power output, and 10m DASH. Results After 4 weeks of RST, significant mprovements were observed in the experimental group. VO2max increased by 4.4 ml/kg/min (95% CI: 2.9 to 6.0; p < 0.001, d = 1.31), and 10m sprint time decreased by 0.32 seconds (95% CI: -0.45 to -0.19; p < 0.001, d = 1.36) in forwards. VJH improved significantly (p < 0.001) among defenders (Δ = 3.44 cm, 95% CI: 1.76 to 5.12, d = 1.06), while power improvements were most notable in defenders (Δ = 43.44W, 95% CI: 28.62 to 58.26, d = 1.00). Goalkeepers showed modest, non-significant improvements. Significant positional differences were identified for VJH and power output (p < 0.001). Conclusion RST significantly enhanced physical performance metrics, particularly for forwards and defenders. The findings emphasize the importance of positional specificity in training programs to optimize football performance.